2006
DOI: 10.1001/jama.295.18.2158
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Visual Impairment in the United States

Abstract: Visual impairment due to uncorrected refractive error is a common condition in the United States. Providing appropriate refractive correction to those individuals whose vision can be improved is an important public health endeavor with implications for safety and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
253
9
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(306 citation statements)
references
References 19 publications
18
253
9
14
Order By: Relevance
“…Other European studies usually have used best-corrected visual acuity and therefore cannot be compared with the present study (Klaver et al 1998;Gunnlaugsdottir et al 2008;Seland et al 2011). In the American NHANES study, performed in 1999-2002, prevalence of visual impairment (presenting visual acuity below 20/40) was 8.8% in subjects aged 60 years or more, which is much lower than the present study (Vitale et al 2006).…”
Section: Discussioncontrasting
confidence: 64%
“…Other European studies usually have used best-corrected visual acuity and therefore cannot be compared with the present study (Klaver et al 1998;Gunnlaugsdottir et al 2008;Seland et al 2011). In the American NHANES study, performed in 1999-2002, prevalence of visual impairment (presenting visual acuity below 20/40) was 8.8% in subjects aged 60 years or more, which is much lower than the present study (Vitale et al 2006).…”
Section: Discussioncontrasting
confidence: 64%
“…Prevalence studies have indicated that correctable visual impairment is a major cause of reduced vision in both developing 19,20 and developed countries. 21,22 When comparing the results of different studies, it should be noted that various definition of correctable visual impairment are used. For example, some studies have defined uncorrected refractive error as an improvement in visual acuity of at least two lines or more in the better eye with the best possible refractive correction.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, estimations showed that approximately 14 million visually-impaired Americans (12 years and older) experienced mental and physical challenges associated with loss of vision [8]. Many studies showed that during the developmental stage of children and adolescents with visual impairment, they continue becoming more vulnerable to life circumstances [9].…”
Section: Introductionmentioning
confidence: 99%